Effect of family work conflict, emotional intelligence and spiritual intelligence on police performance river police full - Ronal Regen; Dahril Dahril; Wahyu Anggara; Maizon Efendi; Damri Damri (Global Econedu, 2021)
This study aims to see the effect of (1) Family work conflict ton the performance of the Sungai Penuh Police Police. (2)Emotional intelligence on the performance of the Sungai Penuh Police Police. (3) Spiritual intelligence on the performance of the Sungai Penuh Police Police. (4)Family work conflict, emotional intelligence and spiritual intelligence together on the performance of the Sungai Penuh Police Police.The population and sample in this study are all Full River Policeas many as 33 people. The technique of determining the number of samples using total sampling. The data analysis technique used multiple regression by fulfilling the requirements of the classical assumption test of normality, and multicollinearity, heteroscedasticity.The results of this study indicate that (1) Work-family conflict has a significant negative effect on ton the performance of the Sungai Penuh Police Police. (2)Emotional intelligence has a significant positive effect on the performance of the Sungai Penuh Police Police. (3) Spiritual intelligence has a significant positive effect on the performance of the Sungai Penuh Police Police. (4) Work-family conflict, emotional intelligence, spiritual intelligence together have a significant effect on the performance of the Sungai Penuh Police Police.